Studi Komposisi Isi Lambung Dan Kondisi Morfometri Untuk Mengetahui Kebiasaan Makan Ikan Manyung (Arius thalassinus) Yang Diperoleh Di Wilayah Semarang - Taunay, Prayoga Nugraha; Wibowo, Edi; Redjeki, Sri (977-2407769)
Manyung fish (Arius thalassinus) is one of the bottom fish (demersal), which has significant economic potential. One of the measures that can be done to preserve the habitat of fish manyung is a rational exploitation. Information on the biological aspects can be provide additional information on the food and feeding habits and the condition of fish manyung morphometry, to gain a better understanding on the survival and growth of fish. The study was conducted to examine the contents of the stomach and the type of food eaten and the condition of morphometry of manyung fish were caught from the waters around Semarang, manyung fish samples obtained from collectors of Semarang in the krobokan. Manyung fish samples taken on July, August, September and October 2011, with total sample of 50 fish. Retrieval of data in this study conducted in the field and in the laboratory by measuring the weight, total length of fish, fish food organisms manyung frequency, and calculate the volume food organisms of fish manyung. Manyung major food fish (Arius thalassinus) by his preponderance index is a kind of fish with a value of 28.7%. Base of composition of stomach contents, types of mouth (sub terminal), the presence of tentacle, and the length of intestines (1,7-2 times length of the body ) can be concluded manyung fish (Arius thalassinus) is omnivores which tend to be carnivores. The results of 50 samples Manyung fish (Arius thalassinus) gained the most long range artifacts in the interval 55-61 cm (23 fish), weight range for most numerous in the interval 1.6 to 2.7 kg (30 fish).